1995
DOI: 10.1007/bf02536300
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that dietary arachidonic acid increases circulating triglycerides

Abstract: Male Syrian hamsters and male CD-1 mice were fed diets supplemented with ethyl esters of oleic, linoleic, arachidonic, and eicosapentaenoic acids (1.1-5%, w/w) for 3-4 wk. Plasma and serum triglycerides were significantly higher in the arachidonic acid-supplemented animals compared to those in the other supplementation groups. Changes in serum insulin and glucose levels did not appear to be related to the changes in circulating triglycerides observed in the arachidonic acid-supplemented group. These data indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The nutrient composition of the diets was calculated from a computerized nutrient data bank using the data from USDA Handbook (8). The Composition of Foods (14) and adjusted to provide at least the recommended daily allowance for known essential nutrients (15).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nutrient composition of the diets was calculated from a computerized nutrient data bank using the data from USDA Handbook (8). The Composition of Foods (14) and adjusted to provide at least the recommended daily allowance for known essential nutrients (15).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the caveat introduced into human feeding studies with AA by the Seyberth et al (3) report, there is considerable interest in the metabolic and physiological effects of dietary AA, although most of the data available currently come from animal experiments (4)(5)(6)(7)(8)(9). AA injected as the free acid intravenously in rabbits causes rapid disseminated intravascular coagulation and the death of the animals (10,11).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Human studies using AA have been limited, probably because of suggestions in the literature that higher levels of AA in the diet may have adverse consequences (5,6). Nevertheless, there have been many feeding studies in animals using high levels of AA that have not shown any major adverse effects (7)(8)(9)(10). Furthermore, several human studies (5,(11)(12)(13) have not resulted in any actual harm to the subjects despite some potential adverse changes in a few physiological parameters such as platelet aggregation in vitro (5).…”
mentioning
confidence: 95%
“…Lp-PLA2 along with triglycerides are major determinants of small dense LDL, a major cardiovascular disease risk factor. In hamster feeding experiments, addition of arachidonic acid to the diet increases blood triglyceride levels (Whelan et al 1995 ). In humans, there is considerable interest in the role of brain arachidonic acid in membrane function and as a precursor for eicosanoids.…”
Section: Discussionmentioning
confidence: 99%